The Role of Accountants in Sustainable Business Practices - Judijanto, Loso; Wijaya, Indra; Wang, Yuanyuan; Herlina, Herlina; Mihardianto, Mihardianto (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Accounting is essential in sustainable business practices because it helps with clear and accurate reporting of environmental, social and governance (ESG) impacts. Accountants are responsible for ensuring that a company's financial reports contain sustainability considerations, which helps companies present information that reflects both their financial performance and the non-financial impact of their actions. Accounting plays an important role in measuring and reporting sustainability-related risks and opportunities. They help companies to identify risks that may impact corporate sustainability and opportunities that can be leveraged to support sustainability initiatives. In addition, accountants help companies comply with applicable sustainability regulations and standards. They ensure that corporate sustainability reports comply with regulations set by regulators and international standards, which increases the credibility and accountability of the report. This compliance also helps companies avoid the legal and reputational problems that non-compliance can cause. In addition, accountants are involved in strategic planning by providing information that supports the formulation of a company's sustainability strategy. They do this by integrating sustainability data into the planning process to ensure that the company's long-term goals align with sustainability initiatives. Overall, accountants help with transparency, accountability, and strategic planning by incorporating sustainability aspects into financial reports and accounting systems.